Behaviour of Steel Arch Stabilized by a Textile Membrane. Issue 1 (October 2015) - Svoboda, O; Machacek, J
Abstract: Behaviour of the slender steel arch supporting textile membranes in a membrane structure with respect to in-plane and out-of plane stability is investigated in the paper. In the last decades the textile membranes have been widely used to cover both common and exclusive structures due to progress in new membrane materials with eminent properties. Nevertheless, complex analysis of such membranes in interaction with steel structure (carbon/stainless steel perimeter or supporting elements) is rather demanding, even with specialized software. Laboratory model of a large membrane structure simulating a shelter roof of a concert stage was tested and the resulting stress/deflection values are presented. The model of a reasonable size was provided with prestressed membrane of PVC coated polyester fabric Ferrari® Précontraint 702S and tested under various loadings. The supporting steel structure consisted of two steel arch tubes from S355 grade steel and perimeter prestressed cables. The stability behaviour of the inner tube was the primary interest of the investigation. The SOFiSTiK software was used to analyse the structural behaviour in 3D. Numerical non-linear analysis of deflections and internal forces of the structure under symmetrical and asymmetrical loadings covers various membrane prestressing and specific boundary conditions. The numerical results are validated using test results. Finally, the preliminary recommendations for appropriate numerical modelling and stability design of the supporting structure are presented.